Jackpot - Stone, Nic (Crown, 2019)
Meet Rico: high school senior and afternoon-shift cashier at the Gas 'n' Go, who after school and work races home to take care of her younger brother. Every. Single. Day. When Rico sells a jackpot-winning lotto ticket, she thinks maybe her luck will finally change, but only if she--with some assistance from her popular and wildly rich classmate Zan--can find the ticket holder who hasn't claimed the prize. But what happens when have and have-nots collide? Will this investigative duo unite...or divide? Nic Stone, the New York Times bestselling author of Dear Martin and Odd One Out, creates two unforgettable characters in one hard-hitting story about class, money--both too little and too much--and how you make your own luck in the world
Hier auch später erschienene, unveränderte Nachdrucke
Keywords: Lotteries / Juvenile fiction; Social classes / Juvenile fiction; Popularity / Juvenile fiction; Families / Georgia / Norcross / Fiction; High school students / Fiction; Lotteries / Fiction; Social classes / Fiction; Popularity / Fiction; Family life / Georgia / Norcross / Fiction; YOUNG ADULT FICTION / Diversity & Multicultural; YOUNG ADULT FICTION / People & Places / United States / African American; YOUNG ADULT FICTION / Social Themes / Class Differences; Lotteries; Social classes; Family life / Fiction; Alltag; Geld; Suche; Sieger; Armut; Soziale Schichtung; Jugend; Lotterie; Schwarze; Freundschaft; Norcross (Ga.) / Fiction; USA; Jugendbuch